Peningkatan Pengetahuan Anak Usia Dini Mengenai Makanan Sehat Melalui Story Telling di PAUD Ibu Bangsa - Nuraini Hakim; Rina Milawati; Neneng Mamduhah; Theresa Testaroja (Jurnal Pengabdian Masyarakat, 2026)
Early childhood is an age group where nutritional needs are crucial. The growth and development of early childhood children falls within a critical period, thus being called the golden age, and they require balanced nutritional intake. Nutrients consumed by the body serve as a source of energy for daily activities, optimal growth and development, learning, and increased immunity, thus preventing illness. Inadequate nutritional intake in early childhood can lead to various health problems. A preliminary study of 10 early childhood education students found that some still bring packaged snacks containing preservatives, sweeteners, and artificial colors. The goal of this activity was to increase student’s knowledge of healthy daily foods through storytelling. Nineteen children aged 5-6 years old participated in the counseling session. After the counseling session, all students were able to answer most of the questions correctly and scored well on the knowledge score. Teachers and parents are recommended to continue promoting healthy foods and preparing healthy snacks daily.